"Our Land Is Not for Sale!" Contesting Oil and Translating Environmental Politics in Amazonian Ecuador. (8th July 2020) - High, Casey
ABSTRACT: In April 2019, Waorani people in Amazonian Ecuador won a key legal battle against plans to sell oil concessions on their indigenous territory. I analyze their engagements with oil as part of an emerging eco‐political "middle ground" characterized by Waorani men working for oil companies and new alliances against oil extraction. Waorani activists lament not the violation of a pristine natural environment separate from themselves and in need of conservation, but instead threats to the qualities of Waorani land ( wao öme ) that allow people and other beings to "live well." In the context of generational changes, their engagement in environmental politics involves translating and moving between different conceptions of indigenous land. While becoming environmental citizens evokes discourses of nature, culture, and stereotypes of Amazonian people as natural conservationists, current eco‐political alliances are based as much on close working relationships with outsiders as symbolic politics. In this context, some Waorani engage productively across different understandings of their territory and its conservation to challenge oil. This middle ground under construction shows that indigenous concepts like wao öme (Waorani land) are not fixed in opposition to "the West" but are integral to thoughtful and strategic engagement in contemporary environmental politics. [Amazonia, middle ground, extractive economies, oil, translation, Waorani, Ecuador] RESUMEN: En abril de 2019 el pueblo Waorani en la Amazonía ecuatoriana ganó una batalla legal contra planes de vender concesiones petroleras en su territorio indígena. En este artículo analizo sus relaciones con petróleo como parte de un emergente "middle ground" politico que se caracteriza por hombres Waorani trabajando en las empresas petroleras y nuevas alianzas contra la extracción de petróleo. Muchos Waorani describen su tierra (wao öme) o territorio (ögïpo) como un nexo de relaciones interdependientes entre seres humanos y no humanos amenezados por la presencia de petróleo. No lamentan la violación de una naturaleza pristina independiente de ellos mismos, sino las amenazas para las cualidades de wao öme que permitan que los humanos y otros seres "viven bien." En el contexto de cambios generacionales y una agenda de desarrollo nacional que promueve "los derechos de la naturaleza, " activistas Waorani dependen de la abilidad de traducir wao öme como "naturaleza" y "cultura." Aunque estas traducciones indican la fragilidad de las alianzas del "middle ground, " algunos adultos jóvenes Waorani hoy en día operan eficazmente a través de tal diferencias para desafiar el petróleo. Este middle ground en construcción demuestra que conceptos indígenas como wao öme no son fijos en oposición a' "occidente, " sino son una parte importante de la participación reflexiva y estretégica en las politícas ambientales. [Amazonía, "middle ground, " economías extractivas, petróleo, traducción, Waorani/Huaorani, Ecuador]